Potential protective role of astrocytes in the pathogenesis of astrocyte-mediated synaptic plasticity of Parkinson’s disease - Yuqi Zhang; Kangrong Lu (Journal of Integrative Neuroscience, 2021)
Astrocytes are the most abundant glia in the central nervous system that play a significant role in disease. Recently, it roles of synaptic plasticity in neuropathological damages have been questioned whether the structural and functional plasticity of synapses contributes to the pathogenesis of Parkinson’s disease. The regulation of synaptic plasticity by astrocytes has also been widely researched based on astrocytes regulate synaptic plasticity by releasing Adenosine triphosphate, glutamate, and D-serine. We discuss the possible role of astrocytes in the regulation of synaptic plasticity, which may provide a new direction to Parkinson’s disease treatment.